Akibat Hukum Pemberlakuan Perjanjian Kerja Bersama Yang Habis Masa Berlakuknya - Rivano, Magasky; Khairani; Fatimah, Titin (Lareh Law Review, 2024)
The form of working relationship between employers and employees is an interdependent relationship. In this relationship, there is an imbalance in the bargaining position between workers and employers, so government intervention is needed to protect workers' rights. So, the government established regulations that require workers and employers to make collective bargaining agreements (PKB). This study uses a normative juridical method with a conceptual approach and a legal synchronization approach. The results of the study found that historically, there has been no clear regulation regarding the way out of expired collective bargaining agreements, and new collective bargaining agreements have not been agreed upon or ratified, both according to Permenaker No. 28 of 2014 and Article 123 of UU No. 13/2003. The legal consequences of the extension of the implementation of the expired Collective Labor Agreement are still valid in its enforcement because, in its implementation, it is in accordance with the rules in Permenaker No. 28 of 2014. However, it will cause potential problems with the renewal of the PKB, which will cause legal uncertainty. This will cause weak legal protection for workers and employers because there is no clarity regarding the maximum limit of enforcement of expired PKB, resulting in the degradation of the guarantee of rights and protection for workers. This uncertainty indicates the need for harmonization and synchronization in the arrangements related to the PKB, and if there is a dispute over industrial relations related to the PKB, it will be resolved quickly and effectively in accordance with the principle of dispute resolution itself.